2017
DOI: 10.1186/s12879-017-2828-4
|View full text |Cite
|
Sign up to set email alerts
|

Health care workers’ knowledge, attitudes and practices on tuberculosis infection control, Nepal

Abstract: BackgroundInfection control remains a key challenge for Tuberculosis (TB) control program with an increased risk of TB transmission among health care workers (HCWs), especially in settings with inadequate TB infection control measures. Poor knowledge among HCWs and inadequate infection control practices may lead to the increased risk of nosocomial TB transmission.MethodsAn institution-based cross-sectional survey was conducted in 28 health facilities providing TB services in the Kathmandu Valley, Nepal. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
56
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 17 publications
(22 reference statements)
12
56
2
4
Order By: Relevance
“…Composite scores were calculated and those scoring ≥70% were considered as having positive attitudes towards COVID-19 control. The cut-off points for knowledge and attitude levels were set as informed by similar studies 5,6 Ethical approval (AD13/479/1769B) was obtained from Ethical Review and Research ethics…”
Section: Strongly Disagree and Disagree = Disagreementioning
confidence: 99%
“…Composite scores were calculated and those scoring ≥70% were considered as having positive attitudes towards COVID-19 control. The cut-off points for knowledge and attitude levels were set as informed by similar studies 5,6 Ethical approval (AD13/479/1769B) was obtained from Ethical Review and Research ethics…”
Section: Strongly Disagree and Disagree = Disagreementioning
confidence: 99%
“…A study among 190 healthcare workers from 28 TB treatment facilities in Nepal found that the overall knowledge and practices of healthcare workers on TB infection control were not satisfactory. [8] This study, however, was limited to only the urban centers, and the knowledge, attitudes, and practices questionnaire did not extend to include the issues speci c to DR TB. Such information could help in the tailored implementation of the guidelines and thus, more effective take-up of the recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Since the treatment supporter system is already in existence to support home-based DOTS, and that all TB patients are required to have one where necessary prior to treatment initiation, such disclosure enhancement interventions centered on treatment supporters could easily be adopted. However, the feasibility and efficacy of such models would need to be evaluated in future randomized trials, and its success would depend largely on the healthcare workers' level of knowledge of TB, an argument supported by the already known positive correlation in knowledge on infection control practices between healthcare workers and household members [24]. Efficacy would also depend on the availability of acceptable TB information aides for use by both patient and treatment supporter, so as to facilitate the disclosure process to household members.…”
Section: Discussionmentioning
confidence: 99%